Molecular Weight Tuning of Organic Semiconductors for Curved Organic–Inorganic Hybrid X‐Ray Detectors. Issue 2 (10th November 2021) - Nanayakkara, M. Prabodhi A.; Masteghin, Mateus G.; Basiricò, Laura; Fratelli, Ilaria; Ciavatti, Andrea; Kilbride, Rachel C.; Jenatsch, Sandra; Webb, Thomas; Richheimer, Filipe; Wood, Sebastian; Castro, Fernando A.; Parnell, Andrew J.; et al.
Abstract: Curved X‐ray detectors have the potential to revolutionize diverse sectors due to benefits such as reduced image distortion and vignetting compared to their planar counterparts. While the use of inorganic semiconductors for curved detectors are restricted by their brittle nature, organic–inorganic hybrid semiconductors which incorporated bismuth oxide nanoparticles in an organic bulk heterojunction consisting of poly(3‐hexylthiophene‐2, 5‐diyl) (P3HT) and [6, 6]‐phenyl C71 butyric acid methyl ester (PC70 BM) are considered to be more promising in this regard. However, the influence of the P3HT molecular weight on the mechanical stability of curved, thick X‐ray detectors remains less well understood. Herein, high P3HT molecular weights (>40 kDa) are identified to allow increased intermolecular bonding and chain entanglements, resulting in X‐ray detectors that can be curved to a radius as low as 1.3 mm with low deviation in X‐ray response under 100 repeated bending cycles while maintaining an industry‐standard dark current of <1 pA mm −2 and a sensitivity of ≈ 0.17 μ C Gy −1 cm −2 . This study identifies a crucial missing link in the development of curved detectors, namely the importance of the molecular weight of the polymer semiconductors used. Abstract : Solution processable organic–inorganic hybrid semiconductors for flexible curved X‐ray detector components have the potential to revolutionize diverse sectors in terms of its cost and performance. This work introduces a strategy for realizing the optimum balance for detector performance at low operating voltages with mechanical flexibility by tuning the organic semiconductor molecular weight for such curved hybrid detectors.